Konsep Hukum Kerjasama Internasional dalam Menghadapi Penyelundupan Senjata Api di Wilayah Perbatasan - Nahria Fahrani Abidin; Johanis Steny Franco Peilouw; Josina Augustina Yvonne Wattimena (Balobe Law Journal, 2023)
Introduction: The prohibition of firearms smuggling in the Palermo convention and its additional protocols is in fact in stark contrast to the fact that firearms smuggling continues to be carried out in the border areas of Southeast Asian countries.Purposes of the Research:  This study aims to find out what are the factors that cause firearms smuggling in border areas, and how the legal concept of international cooperation is in dealing with firearms smuggling in border areas.Methods of the Research: This study uses normative legal research methods, which aims to find out what are the factors that cause firearms smuggling in border areas, and how the legal concept of international cooperation is in dealing with firearms smuggling in border areas.Results of the Research: The cause of the smuggling of firearms in the border region is caused by the activities of terrorist groups in the Southeast Asian region. The activities of these terrorist groups stimulate the emergence of conflicts in border areas, resulting in an increase in the need for weapons transfers which lead to smuggling activities. The fact is that the need for weapons transfer by smuggling also involves countries affected by conflict. In practice, both the state and terrorist groups tend to smuggle firearms because they are more affordable financially and also have a steady market with higher levels of supply. The legal concept of international cooperation that can be offered in dealing with smuggling of firearms in this border region is by using international cooperation between countries using the Mutual Legal Assistance mechanism established according to the 2000 Palermo Convention. The concept of cooperation between countries must be supported by increasing human resource capacity and legal coordination between ASEAN member countries.